High-strength electrolytic copper foil and method for producing the same, electrode and secondary battery

By controlling the crystal plane orientation index and tensile strength of the copper layer, combined with the purification process of the electrolyte and the application of the anti-rust film, the problem of tear and capacity retention in the manufacturing of copper foil film in secondary batteries is solved, and the problem of low tear and capacity retention in the manufacturing of copper foil film in secondary batteries is achieved. The electrolytic copper foil with high strength and elongation is improved, and the capacity retention and life of the secondary battery are improved.

CN114318427BActive Publication Date: 2024-12-13SK NEXILIS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111154275.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-09-29
Publication Date
2024-12-13
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

The copper foil in existing secondary batteries is prone to tear or wrinkles during the thin film manufacturing process, and the capacity retention rate after the charge and discharge cycle is low, resulting in a short secondary battery life, and a need for a high strength under thin thickness. and elongation electrolytic copper foil to improve capacity retention of secondary batteries.

Method used

By controlling the crystal plane orientation index and tensile strength of the copper layer, specific electrolyte composition and manufacturing processes are used, including carbon filtration, celite filtration and ozone treatment, to purify the organic additives to form electrolytic copper with excellent strength and elongation. foil and a rust-proof film is applied to the copper layer to improve its stability.

Benefits of technology

The high strength and elongation of electrolytic copper foil in the form of thin film is realized, tear and wrinkle are prevented, the charging and discharge capacity retention rate and life of the secondary battery are improved, and the defect rate in the manufacturing process is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114318427B_ABST
    Figure CN114318427B_ABST
Patent Text Reader

Abstract

One embodiment of the present invention provides an electrolytic copper foil, the electrolytic copper foil including a copper layer, the copper layer having a (220) plane, and the orientation index [M(220)] of the (220) plane being greater than 1. According to one embodiment of the present invention, an electrolytic copper foil having excellent strength and elongation can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrolytic copper foil which is easy to handle in a manufacturing process and is used to improve the capacity retention rate of a secondary battery, an electrode including the electrolytic copper foil, a secondary battery including the electrode, and a method for manufacturing the electrolytic copper foil. Background Art

[0002] Secondary batteries are a type of energy converter that converts electrical energy into chemical energy and stores it. When electricity is needed, the chemical energy is converted back into electrical energy to generate electricity. Secondary batteries are not only used in portable household appliances such as mobile phones and notebooks, but are also used as energy for electric vehicles.

[0003] As secondary batteries that are economical and environmentally friendly compared to disposable primary batteries, there are lead storage batteries, nickel-cadmium secondary batteries, nickel-hydrogen secondary batteries, lithium secondary batteries, and the like.

[0004] Among these secondary batteries, lithium secondary batteries have high operating voltage, high energy density and excellent life characteristics. Therefore, in the field of information and communication equipment that attaches importance to portability and mobility, lithium secondary batteries are preferred, and their application range is also expanding to energy storage devices for hybrid vehicles and electric vehicles.

[0005] A secondary battery includes a negative electrode collector made of copper foil, and among copper foils, electrolytic copper foil is widely used as a negative electrode collector of a secondary battery. As the demand for secondary batteries increases, the demand for secondary batteries with high capacity, high efficiency and high quality increases, and therefore, a copper foil capable of improving the characteristics of a secondary battery is needed. In particular, a copper foil capable of ensuring high capacity and stable capacity retention of a secondary battery is needed.

[0006] On the other hand, the thinner the copper foil is, the more active material can be contained in the same space, and the number of collectors can be increased, thereby increasing the capacity of the secondary battery. However, as the copper foil becomes thinner, defects such as tearing or wrinkling may occur during the copper foil manufacturing and battery manufacturing processes, so it is difficult to manufacture copper foil in the form of very thin films.

[0007] In addition, even if the secondary battery has a sufficiently high charge / discharge capacity, if the charge / discharge capacity of the secondary battery decreases rapidly as the charge / discharge cycle is repeated (i.e., if the capacity retention rate is low or the life is short), the secondary battery needs to be replaced frequently, which will waste costs and resources economically and environmentally. As one of the reasons for the reduction in the capacity retention rate of the secondary battery, copper foil damage can be cited. As the charge / discharge cycle of the secondary battery is repeated, the negative electrode collector shrinks / expands, and the copper foil may break. Summary of the invention

[0008] Problems to be solved by the invention

[0009] In order to solve the above-mentioned problems of the prior art, an object of the present invention is to provide an electrolytic copper foil having high strength and excellent elongation even in a thin thickness.

[0010] One aspect of the present invention is to provide an electrolytic copper foil that is easy to handle in the copper foil and battery manufacturing process and can improve the capacity retention rate of a secondary battery.

[0011] Another aspect of the present invention is to provide an electrode capable of improving the capacity retention rate of a secondary battery.

[0012] Still another aspect of the present invention is to provide a secondary battery capable of improving the capacity retention rate of the secondary battery.

[0013] Another aspect of the present invention is to provide a method for producing an electrolytic copper foil capable of improving the capacity retention rate of a secondary battery.

[0014] In addition to the above-mentioned modes of the present invention, other features and advantages of the present invention will be described below, or may be clearly understood by a person skilled in the art to which the present invention belongs through these descriptions.

[0015] Technical solutions to the problem

[0016] According to one embodiment of the present invention as described above, there is provided an electrolytic copper foil including a copper layer, wherein the copper layer has a (220) plane, and the orientation index [M(220)] of the (220) plane is 1 or more, wherein the orientation index [M(220)] is obtained by the following formula 1:

[0017] [Formula 1]

[0018] M(220)=IR(220) / IFR(220)

[0019] In the above formula 1, IR(220) and IFR(220) are obtained by the following formula 2 and the following formula 3, respectively.

[0020] [Formula 2]

[0021]

[0022] [Formula 3]

[0023]

[0024] In Formula 2, I(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of the electrolytic copper foil, and in Formula 3, IF(hkl) is the XRD diffraction intensity of each crystal plane (hkl) in the JCPDS card.

[0025] The electrolytic copper foil may have an elongation of 2 to 15% at room temperature.

[0026] The electrolytic copper foil may have a strength of 41.0 to 75.0 kgf / mm at room temperature. 2 tensile strength.

[0027] The electrolytic copper foil may have a strength of 40.0 to 65.0 kgf / mm after heat treatment at 190° C. for 60 minutes. 2 tensile strength.

[0028] The ratio of the tensile strength of the electrolytic copper foil after heat treatment at 190° C. for 60 minutes to the tensile strength at room temperature may be greater than 0.950.

[0029] The electrolytic copper foil may have a thickness of 2.0 to 18.0 μm.

[0030] The electrolytic copper foil may further include a protective layer disposed on the copper layer, and the anti-rust film may include at least one of chromium, a silane compound, and a nitrogen compound.

[0031] According to another aspect of the present invention, there is provided an electrode for a secondary battery, comprising: an electrolytic copper foil; and an active material layer disposed on at least one surface of the electrolytic copper foil, wherein the electrolytic copper foil is any one of the electrolytic copper foils described above.

[0032] According to another embodiment of the present invention, a secondary battery is provided, characterized in that it includes: a positive electrode (cathode); a negative electrode (anode), which is composed of the electrode for the secondary battery; an electrolyte (electrolyte), which provides an environment for the movement of lithium ions between the positive electrode and the negative electrode; and a separator (separator), which electrically insulates the positive electrode and the negative electrode.

[0033] According to another embodiment of the present invention, there is provided a method for manufacturing an electrolytic copper foil, comprising: preparing an electrolyte containing copper ions and an organic additive; and energizing an anode plate and a rotating cathode roller arranged in a manner separated from each other in the electrolyte at a current density to form a copper layer, and further comprising: purifying the organic additive by at least one of carbon filtration, diatomaceous earth filtration, and ozone treatment, wherein the step of preparing the electrolyte comprises: heat-treating a copper wire; pickling the heat-treated copper wire; washing the pickled copper wire with water; and placing the washed copper wire into sulfuric acid for an electrolyte, wherein the electrolyte comprises: 80 to 120 g / L of copper ions; 80 to 150 g / L of sulfuric acid; and 0.01 to 1.5 ppm of chloride ions (Cl -), the organic additive includes a grain regulator, the grain regulator includes an organic compound, and the organic compound contains an amino group, a carboxyl group (-COOH) and a thiol group (-SH).

[0034] The carbon filtration may use at least one of granule carbon and flake carbon.

[0035] The crystal grain regulator may include at least one selected from the group consisting of collagen, gelatin, and decomposed products of collagen and gelatin.

[0036] The concentration of the grain conditioner may be 0.5 to 15.0 ppm.

[0037] The electrolyte may have a total organic carbon (TOC) concentration of 50 ppm or less.

[0038] The method for manufacturing the electrolytic copper foil may further include: forming a protective layer on the copper layer using an anti-rust liquid, wherein the anti-rust liquid may contain at least one of chromium, a silane compound, and a nitrogen compound.

[0039] Effects of the Invention

[0040] According to one embodiment of the present invention, it is possible to provide an electrolytic copper foil having an orientation index of the (220) plane of 1 or more. In addition, according to one embodiment of the present invention, it is possible to provide an electrolytic copper foil having excellent strength and elongation.

[0041] According to another embodiment of the present invention, a method for producing an electrolytic copper foil having an orientation index of a (220) plane of 1 or more and excellent strength and elongation can be provided.

[0042] This can prevent the copper foil or the secondary battery from being torn or wrinkled during the manufacturing process, and can provide a secondary battery that can maintain a high charge and discharge capacity even when the charge and discharge cycles are repeated. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The accompanying drawings are used to help the understanding of the present invention and constitute a part of this specification. They illustrate embodiments of the present invention and, together with the detailed description of the invention, are used to explain the principles of the present invention.

[0044] Figure 1 This is a schematic cross-sectional view of an electrolytic copper foil according to an embodiment of the present invention.

[0045] Figure 2 This is an example of an XRD spectrum of an electrolytic copper foil.

[0046] Figure 3It is a schematic cross-sectional view of an electrolytic copper foil according to another embodiment of the present invention.

[0047] Figure 4 This is a schematic cross-sectional view of an electrolytic copper foil according to still another embodiment of the present invention.

[0048] Figure 5 This is a schematic cross-sectional view of a secondary battery electrode according to still another embodiment of the present invention.

[0049] Figure 6 This is a schematic cross-sectional view of a secondary battery electrode according to still another embodiment of the present invention.

[0050] Figure 7 is a schematic cross-sectional view of a secondary battery according to still another embodiment of the present invention.

[0051] Figure 8 This is a photo of granular carbon.

[0052] Fig. 9 This is a photo of carbon fragments.

[0053] Fig.10 This is a diagram of a cross section of an electrolytic copper foil at room temperature taken by EBSD according to Example 1 of the present invention.

[0054] Fig.11 This is a cross-sectional view of the electrolytic copper foil of Example 1 of the present invention taken by EBSD after heat treatment at 190° C. for 1 hour.

[0055] Fig.12 This is a diagram of a cross section of an electrolytic copper foil at room temperature taken by EBSD according to Example 2 of the present invention.

[0056] Fig.13 This is a cross-sectional view of the electrolytic copper foil of Example 2 of the present invention taken by EBSD after heat treatment at 190° C. for 1 hour.

[0057] Description of Reference Numerals

[0058] 101, 102, 103: Electrolytic copper foil

[0059] 120, 130: first protective layer and second protective layer

[0060] 201, 202: Electrodes for secondary batteries

[0061] 210, 220: first active material layer and second active material layer

[0062] 300: Secondary battery DETAILED DESCRIPTION

[0063] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0064] It is obvious to those skilled in the art that various changes and modifications can be made to the present invention without exceeding the technical concept and scope of the present invention. Therefore, the present invention includes all changes and modifications within the scope of the invention described in the claims and their equivalents.

[0065] The shapes, sizes, ratios, angles, quantities, etc. disclosed in the accompanying drawings for illustrating the embodiments of the present invention are exemplary, and therefore, the present invention is not limited by the contents shown in the accompanying drawings. Throughout the specification, the same constituent elements may be represented by the same reference numerals.

[0066] When the words "including", "having", "consisting of", etc. are used in this specification, other parts may be added unless the expression "only" is used. When a constituent element is expressed in the singular, the plural number is included unless otherwise explicitly stated. Furthermore, when interpreting a constituent element, it is interpreted as including a tolerance range even if there is no separate explicit description.

[0067] When describing the positional relationship, for example, when describing the positional relationship of two parts by using "on ...", "upper ...", "lower ...", "beside ...", etc., one or more other parts may be provided between the two parts, unless the expression "directly" or "directly" is used.

[0068] When describing a temporal relationship, for example, when describing a temporal sequence using "afterwards", "subsequently", "next", "before", etc., discontinuous situations may also be included unless the expression "immediately" or "directly" is used.

[0069] In order to explain various components, expressions such as "first" and "second" are used, but these components are not limited by these terms. These terms are only used to distinguish one component from another component. Therefore, within the technical concept of the present invention, the first component mentioned below can be the second component.

[0070] The term "at least one" should be understood to include all combinations that can be given from more than one of the related items.

[0071] Each feature of each embodiment of the present invention may be partially or entirely combined or combined with each other, may be technically linked and driven in various ways, and each embodiment may be implemented independently of each other, or may be implemented together in an associated relationship.

[0072] Figure 1 1 is a schematic cross-sectional view of an electrolytic copper foil 101 according to an embodiment of the present invention.

[0073] like Figure 1 As shown, an electrolytic copper foil 101 according to an embodiment of the present invention includes a copper layer 110. The copper layer 110 has a matte surface MS and a shiny surface SS opposite to the matte surface MS.

[0074] For example, the copper layer 110 can be formed on the rotating cathode roller by electroplating. At this time, the smooth surface SS refers to the surface that has been in contact with the rotating cathode roller during the electroplating process, and the matte surface MS refers to the opposite surface of the smooth surface SS. Figure 1 In the figure, the matte surface MS refers to the "upper surface" of the electrolytic copper foil 101, and the smooth surface SS refers to the "lower surface" of the electrolytic copper foil. However, the "upper surface" and "lower surface" are described for the convenience of describing the present invention, and the matte surface MS may also be the "lower surface" and the smooth surface SS may also be the "upper surface".

[0075] According to an embodiment of the present invention, the copper layer 110 has a crystal plane, and the crystal plane of the copper layer 110 can be represented by a (hkl) plane.

[0076] More specifically, the copper layer 110 has a plurality of crystal planes, which can be represented by Miller Index. The crystal planes of the copper layer 110 may include (111) plane, (200) plane, (220) plane, and (311) plane. Each of these crystal planes has a diffraction intensity, and the diffraction intensity of the crystal plane can be measured or calculated using X-ray diffraction (XRD).

[0077] According to an embodiment of the present invention, among the crystal planes of the copper layer 110 , the orientation index (Orientation Index, M) of the (220) plane is greater than 1. The orientation index [M(220)] of the (220) plane is obtained by the following formula 1.

[0078] [Formula 1]

[0079] M(220)=IR(220) / IFR(220)

[0080] IR(220) and IFR(220) in the above formula 1 are obtained by the following formula 2 and the following formula 3, respectively.

[0081] [Formula 2]

[0082]

[0083] [Formula 3]

[0084]

[0085] In Formula 2, I(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of the electrolytic copper foil 101, and I(220) is the XRD diffraction intensity of the (220) plane of the electrolytic copper foil 101. In Formula 3, IF(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of a standard sample with no orientation relative to all crystal planes as specified by JCPDS (Joint Committee on Powder Diffraction Standards), and IF(220) is the XRD diffraction intensity of the (220) plane of the standard sample.

[0086] Below, refer to Figure 2 , a method for measuring and calculating the orientation index [M(220)] of the (220) plane among the crystal planes of the copper layer 110 constituting the electrolytic copper foil 101 is described.

[0087] Figure 2 is an example of an XRD spectrum of the electrolytic copper foil 101. More specifically, Figure 2 This is an XRD spectrum of the copper layer 110 constituting the electrolytic copper foil 101 . Figure 2 The peaks correspond to different crystal planes. Figure 2 The XRD spectrum of is only an example, and the XRD spectrum of the electrolytic copper foil may vary according to the copper foil, and the present invention is not limited thereto.

[0088] The orientation index [M(hkl)] of the crystal plane (hkl) of the copper layer 110 is a value obtained by dividing the relative diffraction intensity [IR(hkl)] with respect to a specific crystal plane (hkl) of the copper layer 110 by the relative diffraction intensity [IFR(hkl)] with respect to the specific crystal plane (hkl) obtained from a standard sample that is not oriented with respect to all crystal planes.

[0089] In order to measure the relative diffraction intensity [IR(hkl)] relative to a specific crystal plane (hkl) of the copper layer 110, first, an XRD spectrum having peaks corresponding to each crystal plane is obtained by X-ray diffraction (XRD) within a diffraction angle range of 30° to 95° [target: copper Kα1, 2θ spacing: 0.01°, 2θ scanning speed: 1° / min].

[0090] Reference Figure 2 , an XRD spectrum including four peaks corresponding to the (111) plane, the (200) plane, the (220) plane, and the (311) plane is obtained from the copper layer 110. Then, the XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) is obtained from the spectrum. The XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) obtained by the above method is substituted into the formula 2 to calculate the relative diffraction intensity [IR(220)] relative to the specific crystal plane (220) of the copper layer 110.

[0091] In addition, the relative diffraction intensity [IFR(220)] of a specific crystal plane (220) obtained from a standard sample that is not oriented relative to all crystal planes can be calculated by substituting the XRD diffraction intensity [IF(hkl)] of each crystal plane (hkl) of the standard sample that is not oriented relative to all crystal planes specified by JCPDS into the above formula 3.

[0092] By substituting [IR(220)] and [IFR(220)] obtained according to Formula 2 and Formula 3 into Formula 1, the orientation index [M(220)] of the (220) plane among the crystal planes of the copper layer 110 can be calculated.

[0093] According to one embodiment of the present invention, the orientation index [M(220)] of the (220) plane among the crystal planes of the copper layer 110 is greater than 1. If the orientation index [M(220)] of the (220) plane is greater than 1, the copper layer 110 has a preferred orientation parallel to the (220) plane. If the orientation index [M(220)] of the (220) plane is less than 1, it indicates that the preferred orientation is reduced.

[0094] If the orientation index [M(220)] of the (220) plane of the copper layer 110 is less than 1, the preferred orientation of the (220) plane of the copper layer 110 is reduced, thereby causing the crystalline structure of the copper layer 110 to be too fine, thereby increasing the tensile strength of the copper layer 110 at room temperature to be 75.0 kgf / mm 2 The possibility of the copper layer 110 having an ultra-high strength is increased, and the mixing of impurities is increased. Therefore, the occurrence rate of electrodeposition defects of the electrolytic copper foil 101, such as pinholes, is also increased, and as a result, the tensile strength of the electrolytic copper foil 101 after high-temperature heat treatment is relatively greatly reduced, and the elongation at room temperature is reduced, so that tearing or wrinkling may occur in the electrolytic copper foil 101.

[0095] According to an embodiment of the present invention, the electrolytic copper foil 101 may have an elongation of 2 to 15% at room temperature (25±15° C.).

[0096] The elongation of the electrolytic copper foil 101 can be measured by a universal testing machine (UTM) according to the method specified in the IPC-TM-650 Test Method Manual. According to one embodiment of the present invention, an apparatus of Instron can be used. At this time, the width of the sample for elongation measurement is 12.7 mm, the distance between the grips is 50 mm, and the measurement speed is 50 mm / min.

[0097] If the elongation of the electrolytic copper foil 101 at room temperature is less than 2%, the tearing rate of the electrolytic copper foil 101 in the roll-to-roll process in the copper foil manufacturing process increases, and when the electrolytic copper foil 101 is used as a collector of a secondary battery, there is a risk that the electrolytic copper foil 101 cannot be fully stretched corresponding to the large volume expansion of the high-capacity active material and may tear. On the contrary, if the elongation exceeds 15% and becomes too large, the electrolytic copper foil 101 is easily stretched in the secondary battery manufacturing process, thereby causing deformation of the electrode.

[0098] According to an embodiment of the present invention, the electrolytic copper foil 101 may have a thermal conductivity of 41.0 to 75.0 kgf / mm at room temperature (25±15° C.). 2 tensile strength.

[0099] The tensile strength of the electrolytic copper foil 101 can be measured using a universal testing machine (UTM) according to the method specified in the IPC-TM-650 Test Method Manual. According to one embodiment of the present invention, an apparatus from Instron can be used. At this time, the width of the sample for elongation measurement is 12.7 mm, the distance between the grips is 50 mm, and the measurement speed is 50 mm / min.

[0100] If the tensile strength of the electrolytic copper foil 101 at room temperature is less than 41.0 kgf / mm 2 , the electrolytic copper foil 101 is easily deformed by the force applied to it in the roll-to-roll process in the copper foil manufacturing process or the secondary battery manufacturing process, thereby causing the risk of tearing or wrinkling. On the contrary, if the tensile strength of the electrolytic copper foil 101 exceeds 75.0 kgf / mm 2 , as the electrolytic copper foil 101 is subjected to tension during the copper foil manufacturing process, the risk of tearing increases, and the workability of the secondary battery manufacturing process is reduced.

[0101] According to an embodiment of the present invention, the electrolytic copper foil 101 may have a strength of 40.0 to 65.0 kgf / mm after being heat treated at 190° C. for 60 minutes. 2 tensile strength.

[0102] The tensile strength of the electrolytic copper foil 101 after heat treatment can be measured by using a universal testing machine (UTM) according to the method specified in the IPC-TM-650 Test Method Manual for the electrolytic copper foil 101 heat treated at 190°C for 60 minutes. According to one embodiment of the present invention, an apparatus of Instron can be used. At this time, the width of the sample for elongation measurement is 12.7 mm, the distance between the grips is 50 mm, and the measurement speed is 50 mm / min.

[0103] After heat treatment at 190°C for 60 minutes, the tensile strength of the electrolytic copper foil 101 is less than 40.0 kgf / mm 2 , there is a risk of wrinkles in the roll-to-roll process in the copper foil manufacturing process or the secondary battery manufacturing process due to the low strength of the electrolytic copper foil 101. On the contrary, if the tensile strength of the electrolytic copper foil 101 after heat treatment exceeds 65.0 kgf / mm 2 , the copper foil will break during the secondary battery manufacturing process due to the decrease in elongation.

[0104] According to an embodiment of the present invention, the ratio of the tensile strength of the electrolytic copper foil 101 after heat treatment at 190° C. for 60 minutes to the tensile strength at room temperature (25±15° C.) may be greater than 0.950. This can be expressed by the following formula 4.

[0105] [Formula 4]

[0106]

[0107] If the ratio of the tensile strength after heat treatment at 190°C for 60 minutes to the tensile strength at room temperature (25±15°C) is less than 0.950, the strength of the electrolytic copper foil 101 after heat treatment decreases, and the foil 101 may break due to volume expansion during the charge and discharge of the secondary battery. The breakage of the electrolytic copper foil 101 reduces the charge and discharge efficiency of the secondary battery.

[0108] According to an embodiment of the present invention, the electrolytic copper foil 101 may have a thickness of 2.0 to 18.0 μm.

[0109] When the electrolytic copper foil 101 is used as a collector of an electrode in a secondary battery, the thinner the thickness of the electrolytic copper foil 101, the more collectors can be accommodated in the same space, which is conducive to realizing the high capacity of the secondary battery. Therefore, when the thickness of the electrolytic copper foil 101 exceeds 18.0 μm, the thickness of the electrode for the secondary battery using the electrolytic copper foil 101 increases, and due to this thickness, it may be difficult to achieve a high capacity of the secondary battery. On the contrary, when the thickness of the electrolytic copper foil 101 is less than 2.0 μm, the processability of the electrode for the secondary battery using the electrolytic copper foil 101 and the manufacturing process of the secondary battery is significantly reduced.

[0110] According to another embodiment of the present invention, the electrolytic copper foil 102 may further include a first protective layer 120 disposed on the copper layer 110. In order to avoid repetition, the description of the components that have been described will be omitted.

[0111] Figure 3 FIG. 1 is a schematic cross-sectional view of an electrolytic copper foil 102 according to another embodiment of the present invention. Figure 3 , the electrolytic copper foil 102 including the first protective layer 120 is described.

[0112] The first protective layer 120 is disposed on at least one side of the copper layer 110. Figure 3 , the first protection layer 120 is disposed on the upper surface of the copper layer 110 . However, an embodiment of the present invention is not limited thereto, and the first protection layer 120 may also be disposed on the lower surface of the copper layer 110 .

[0113] The protective layer 120 can protect the copper layer 110 to prevent the copper layer 110 from being oxidized or deteriorated during storage or circulation. Therefore, the protective layer 120 is also called an anti-rust film.

[0114] According to another embodiment of the present invention, the first protection layer 120 may include at least one of chromium (Cr), a silane compound, and a nitrogen compound.

[0115] According to another embodiment of the present invention, the orientation index (OrientationIndex, M) of the (220) plane among the crystal planes of the copper layer 110 is greater than 1.

[0116] According to another embodiment of the present invention, the electrolytic copper foil 102 may have an elongation of 2 to 15% at room temperature (25±15° C.).

[0117] According to another embodiment of the present invention, the electrolytic copper foil 102 may have a thermal conductivity of 41.0 to 75.0 kgf / mm at room temperature (25±15° C.). 2 tensile strength.

[0118] According to another embodiment of the present invention, the electrolytic copper foil 102 may have a strength of 40.0 to 65.0 kgf / mm after being heat treated at 190° C. for 60 minutes. 2 tensile strength.

[0119] According to another embodiment of the present invention, the ratio of the tensile strength of the electrolytic copper foil 102 after heat treatment at 190° C. for 60 minutes to the tensile strength at room temperature (25±15° C.) may be greater than 0.950.

[0120] According to another embodiment of the present invention, the electrolytic copper foil 102 may have a thickness of 2.0 to 18.0 μm.

[0121] According to another embodiment of the present invention, the electrolytic copper foil 103 may further include a second protective layer 130 disposed on the copper layer 110. In order to avoid repetition, the description of the components that have been described will be omitted.

[0122] Figure 4 FIG. 1 is a schematic cross-sectional view of an electrolytic copper foil 103 according to another embodiment of the present invention. Figure 4 , the electrolytic copper foil 103 including the second protective layer 130 is described.

[0123] like Figure 4 As shown, the second protection layer 130 may be disposed on the opposite side of the copper layer 110 to the side on which the first protection layer 120 is disposed. Figure 1 Compared with the electrolytic copper foil 101 shown, Figure 4 The electrolytic copper foil 103 shown includes: a copper layer 110 ; and a first protective layer 120 and a second protective layer 130 respectively disposed on two sides of the copper layer 110 .

[0124] According to another embodiment of the present invention, the second protection layer 130 may include at least one of chromium (Cr), a silane compound, and a nitrogen compound.

[0125] According to another embodiment of the present invention, the orientation index (OrientationIndex, M) of the (220) plane among the crystal planes of the copper layer 110 is greater than 1.

[0126] According to another embodiment of the present invention, the electrolytic copper foil 103 may have an elongation of 2 to 15% at room temperature (25±15° C.).

[0127] According to another embodiment of the present invention, the electrolytic copper foil 103 may have a thermal conductivity of 41.0 to 75.0 kgf / mm at room temperature (25±15° C.). 2 tensile strength.

[0128] According to another embodiment of the present invention, the electrolytic copper foil 103 may have a strength of 40.0 to 65.0 kgf / mm after being heat treated at 190° C. for 60 minutes. 2 tensile strength.

[0129] According to another embodiment of the present invention, the ratio of the tensile strength of the electrolytic copper foil 103 after heat treatment at 190° C. for 60 minutes to the tensile strength at room temperature (25±15° C.) may be greater than 0.950.

[0130] According to another embodiment of the present invention, the electrolytic copper foil 103 may have a thickness of 2.0 to 18.0 μm.

[0131] Figure 5 1 is a schematic cross-sectional view of a secondary battery electrode 201 according to still another embodiment of the present invention. Figure 5 The secondary battery electrode 201 shown can be applied to, for example, Figure 7 A secondary battery 300 is shown.

[0132] Reference Figure 5 A secondary battery electrode 201 according to another embodiment of the present invention includes an electrolytic copper foil 102 and an active material layer 210 disposed on the electrolytic copper foil 102. Here, the electrolytic copper foil 102 includes a copper layer 110 and a first protective layer 120 disposed on the copper layer 110, and serves as a current collector.

[0133] Specifically, the active material layer 210 may be disposed on at least one side of the electrolytic copper foil 102. Figure 5 The active material layer 210 may be disposed on the first protective layer 120 . However, an embodiment of the present invention is not limited thereto, and the active material layer 210 may also be disposed on the lower surface of the copper layer 110 .

[0134] Figure 5 It is shown in Figure 3 The electrolytic copper foil 102 is used as an example of a current collector. However, another embodiment of the present invention is not limited to this, and it is also possible to use Figure 1 The electrolytic copper foil 101 or Figure 4 The electrolytic copper foil 103 shown is used as a current collector of the secondary battery electrode 201 .

[0135] In addition, although Figure 5 , the structure in which the active material layer 210 is arranged only on one side of the electrolytic copper foil 102 is shown, but another embodiment of the present invention is not limited thereto, and the active material layers 210 and 220 may be arranged on both sides of the electrolytic copper foil 102. In addition, the active material layer 210 may be arranged only on the side of the electrolytic copper foil 102 opposite to the side on which the first protective layer is arranged.

[0136] Figure 5The active material layer 210 shown is composed of an electrode active material, and in particular, can be composed of a negative electrode active material. Figure 5 The secondary battery electrode 201 shown can be used as a negative electrode.

[0137] The active material layer 210 may include at least one of carbon, metal, metal-containing alloy, metal oxide, and metal-carbon composite as a negative electrode active material. As the metal, at least one of Si, Ge, Sn, Li, Zn, Mg, Cd, Ce, Ni, and Fe may be used. In addition, the active material layer 210 may include silicon (Si) to increase the charge and discharge capacity of the secondary battery.

[0138] As the secondary battery is repeatedly charged and discharged, the active material layer 210 shrinks and expands alternately, which causes the active material layer 210 and the copper foil 102 to separate, thereby reducing the charge and discharge efficiency of the secondary battery. In particular, the active material layer 210 containing silicon (Si) expands and shrinks to a greater extent.

[0139] According to another embodiment of the present invention, since the electrolytic copper foil 102 used as a current collector can shrink and expand corresponding to the shrinkage and expansion of the active material layer 210, even if the active material layer 210 shrinks and expands, the electrolytic copper foil 102 will not be deformed or torn. As a result, separation does not occur between the electrolytic copper foil 102 and the active material layer 210. Therefore, a secondary battery including such a secondary battery electrode 201 has excellent charge and discharge efficiency and excellent capacity retention rate.

[0140] Figure 6 1 is a schematic cross-sectional view of a secondary battery electrode 202 according to still another embodiment of the present invention.

[0141] A secondary battery electrode 202 according to another embodiment of the present invention includes an electrolytic copper foil 103 and active material layers 210 and 220 disposed on the electrolytic copper foil 103. The electrolytic copper foil 103 includes a copper layer 110 and rust-proof films 120 and 130 disposed on both surfaces of the copper layer 110.

[0142] Specifically, Figure 6 The secondary battery electrode 202 shown includes two active material layers 210 and 220 respectively arranged on both sides of the electrolytic copper foil 103. For the sake of convenience, the active material layer 210 arranged on the upper surface of the electrolytic copper foil 103 is also referred to as the first active material layer, and the active material layer 220 arranged on the lower surface of the electrolytic copper foil 103 is referred to as the second active material layer.

[0143] The two active material layers 210 and 220 may be made of the same material and by the same method, or may be made of different materials or by different methods.

[0144] Figure 7 is a schematic cross-sectional view of a secondary battery 300 according to another embodiment of the present invention. For example, Figure 7 The secondary battery 300 shown is a lithium secondary battery.

[0145] Reference Figure 7 , the secondary battery 300 includes: a positive electrode (cathode) 370; a negative electrode (anode) 340; an electrolyte (electrolyte) 350, which is arranged between the positive electrode 370 and the negative electrode 340 to provide an environment in which ions can move; and a separator (separator) 360, which electrically insulates the positive electrode 370 and the negative electrode 340. Here, for example, the ions moving between the positive electrode 370 and the negative electrode 340 are lithium ions. The separator 360 separates the positive electrode 370 from the negative electrode 340 to prevent the charge generated at one electrode from moving to the other electrode through the interior of the secondary battery 300 and being consumed uselessly. Reference Figure 7 , the separator 360 is disposed in the electrolyte 350 .

[0146] The positive electrode 370 includes a positive electrode current collector 371 and a positive electrode active material layer 372 . Aluminum foil can be used as the positive electrode current collector 371 .

[0147] The negative electrode 340 includes a negative electrode current collector 341 and a negative electrode active material layer 342 . A copper foil can be used as the negative electrode current collector 341 .

[0148] According to one embodiment of the present invention, the negative electrode current collector 341 may be Figure 1 , Figure 3 or Figure 4 The disclosed copper foils 101, 102, and 103. Figure 5 or Figure 6 The secondary battery electrodes 201 and 202 shown can be used as Figure 7 The negative electrode 340 of the secondary battery 300 is shown.

[0149] Hereinafter, a method for producing an electrolytic copper foil according to an embodiment of the present invention will be described in detail.

[0150] The method for producing an electrolytic copper foil of the present invention comprises: preparing an electrolyte containing copper ions and an organic additive; and energizing an anode plate and a rotating cathode drum disposed in a spaced-apart manner in the electrolyte at a current density to form a copper layer.

[0151] In addition, the method for manufacturing the electrolytic copper foil of the present invention further comprises: a step of purifying the organic additive by at least one of carbon filtration, diatomaceous earth filtration and ozone treatment.

[0152] Specifically, an electrolyte solution containing copper ions and an organic additive is prepared and contained in an electrolytic cell.

[0153] The organic additive is purified by at least one of carbon filtration, diatomaceous earth filtration, and ozone treatment. The purification step of the organic additive can be performed in the state of an organic additive solution before adding the organic additive to the electrolyte, or in the state of an electrolyte after adding the organic additive to the electrolyte. Therefore, the step of purifying the organic additive can be performed before the step of preparing the electrolyte, can be performed after the step of preparing the electrolyte, or can be performed simultaneously.

[0154] Next, at 40 to 70 ASD (A / dm 2 ) current density is applied to the anode plate and the rotating cathode roller, which are spaced apart from each other in the electrolyte, to form a copper layer. The copper layer is formed by the principle of electroplating. The interval between the anode plate and the rotating cathode roller can be controlled within the range of 5 to 20 mm.

[0155] If the current density applied between the anode plate and the rotating cathode drum is less than 40 ASD, the grain formation of the copper layer is increased, and if it exceeds 70 ASD, the grain refinement is accelerated. More specifically, the current density can be preferably adjusted to 45 ASD or more.

[0156] The surface properties of the copper layer in the direction in contact with the rotating cathode roller may differ depending on the degree of polishing or grinding of the surface of the rotating cathode roller. In order to adjust the surface properties of the copper layer in the direction in contact with the rotating cathode roller, for example, the surface of the rotating cathode roller may be ground with a grinding brush having a grit of #800 to #3000.

[0157] During the formation of the copper layer, the electrolyte is maintained at a temperature of 40 to 70° C. More specifically, the temperature of the electrolyte is preferably maintained above 45° C. The flow rate of the electrolyte circulation is 20 to 60 m / s. 3 At this time, the physical, chemical and electrical properties of the copper layer can be controlled by adjusting the composition of the electrolyte.

[0158] According to one embodiment of the present invention, the electrolyte comprises 80 to 120 g / L of copper ions, 80 to 150 g / L of sulfuric acid, 0.01 to 1.5 ppm of chloride ions (Cl - ) and organic additives.

[0159] In order to smoothly form the copper layer by copper electrodeposition, the copper ion concentration and the sulfuric acid concentration in the electrolyte are adjusted to 80 to 120 g / L and 80 to 150 g / L, respectively.

[0160] In one embodiment of the present invention, for example, chloride ions (Cl -) can be used to remove silver (Ag) ions that flow into the electrolyte during the formation of the copper layer. Specifically, chloride ions (Cl - ) can cause silver (Ag) ions to precipitate in the form of silver chloride (AgCl). The above silver chloride (AgCl) can be removed by filtration.

[0161] In the chloride ion (Cl - ) concentration is less than 0.01ppm, silver (Ag) ions cannot be removed smoothly. On the contrary, in the case of chloride ions (Cl - ) concentration exceeds 1.5ppm, it may be caused by excessive chloride ions (Cl - ) and produce unnecessary reactions. Therefore, the chloride ions (Cl - ) concentration is controlled at 0.01 to 1.5 ppm. More specifically, chloride ions (Cl - ) concentration can be controlled below 1 ppm, for example, can be controlled in the range of 0.1 to 1 ppm.

[0162] According to one embodiment of the present invention, the organic additive contained in the electrolyte includes a grain regulator. The grain regulator includes an organic compound having an amino group (-NR2) and a carboxyl group (-COOH). R of the amino group is a substituent such as hydrogen (H) or an alkyl group, and the substituent is not particularly limited. That is, the grain regulator can be an organic compound including one or more amino groups and one or more carboxyl groups in one molecule.

[0163] The grain control agent adjusts the size of the crystalline structure of the copper layer by controlling the size of the copper plating particles of the electrolytic copper foil, thereby adjusting the orientation index of the crystal plane of the copper layer.

[0164] The concentration of the grain modifier may be 0.5 to 15.0 ppm. More specifically, the concentration of the grain modifier is preferably 0.5 to 5.0 ppm.

[0165] When the concentration of the grain regulator is less than 0.5 ppm, the tensile strength after high temperature (190°C, 60 minutes) heat treatment is less than 40.0 kgf / mm 2 On the contrary, when the concentration exceeds 15ppm, the tensile strength after heat treatment at high temperature (190℃, 60 minutes) exceeds 65.0kgf / mm 2 Electrolytic copper foil.

[0166] According to one embodiment of the present invention, the organic compound of the grain regulator may further include one or more thiol groups (-SH). That is, the organic compound may include one or more amino groups, one or more carboxyl groups, and one or more thiol groups in one molecule. The grain regulator may contain a cysteine ​​structure. In the case of including a grain regulator containing a cysteine ​​structure, self-annealing of the copper foil after heat treatment can be prevented. In addition, the grain regulator containing a cysteine ​​structure prevents the coarsening of the crystalline structure of the copper layer, makes the (220) plane orientation index of the copper layer greater than 1, and can manufacture a copper foil having high strength and high heat resistance.

[0167] According to one embodiment of the present invention, for example, the crystal modifier may include at least one selected from collagen, gelatin, and decomposition products of collagen and gelatin. Collagen and gelatin may include all low molecular weight substances and high molecular weight substances. Collagen and gelatin preferably contain cysteine ​​structures.

[0168] Collagen and gelatin are substances added to the electrolyte to control the size of the copper-plated particles in the electrolyte and the orientation index of the (220) plane in the crystal plane of the copper layer, and to improve the strength of the electrolytic copper foil.

[0169] According to one embodiment of the present invention, the method for manufacturing the electrolytic copper foil of the present invention may further include: a step of purifying the organic additive. Specifically, the step of purifying the organic additive refers to a purification step of improving the purity of the organic additive by removing organic impurities and inorganic impurities, such as various oils, chlorine (Cl), etc., present in the organic additive or the electrolyte, for example, at least one of carbon filtration, diatomaceous earth filtration and ozone treatment may be used.

[0170] Instead of performing the purification step for the organic additives, the high strength of the electrolytic copper foil can also be achieved by increasing the concentration of the grain regulator. However, when the concentration of the grain regulator is simply increased, the concentration of organic impurities or inorganic impurities also increases, which greatly reduces the elongation of the electrolytic copper foil, reduces the output rate in the manufacturing process, and may also cause scratches on the appearance of the electrolytic copper foil.

[0171] In addition to organic additives, organic impurities and inorganic impurities are also present in the organic additives added to the electrolyte. The organic impurities and inorganic impurities mentioned above will increase the content of organic or inorganic matter in the electrolyte, thereby affecting the electrodeposition of the electrolytic copper foil. For example, if the chlorine (Cl) content in the electrolyte increases, the (220) plane orientation index of the electrolytic copper foil will decrease, and the tensile strength will also decrease.

[0172] In the step of purifying the organic additive, before or after the organic additive is added to the electrolyte, the organic impurities and inorganic impurities that are incidentally present are removed so that the (220) plane orientation index of the electrolytic copper foil is greater than 1 and the tensile strength is 41.0 kgf / mm 2 Above, the elongation is 2% or more.

[0173] According to one embodiment of the present invention, the step of purifying the organic additive may include at least one of filtering the organic additive using carbon (carbon filtration), filtering the organic additive using diatomaceous earth (diatomaceous earth filtration), and treating the organic additive using ozone (O3) (ozone treatment).

[0174] Carbon filtration uses carbon for filtration to remove organic and inorganic impurities in organic additives. The carbon for filtration used in carbon filtration is activated carbon, which is a combination of carbons that include multiple micropores in one particle. The micropores of the carbon for filtration form a wide surface area inside the carbon, which can have excellent physical and chemical adsorption. The excellent adsorption of carbon for filtration can absorb and adsorb impurities present in organic additives and remove them.

[0175] According to an embodiment of the present invention, the filtering carbon used in the carbon filtering may include at least one of granule carbon and fragment carbon.

[0176] Figure 8 This is a photo of granular carbon. Fig. 9 This is a photo of carbon fragments. Both granular carbon and carbon fragments are activated carbon. There is no difference in their composition. They only differ in surface area and adsorption due to their different shapes. Figure 8 and Fig. 9 As shown, the granular carbon has a cylindrical shape, while the flake carbon has a thin and uneven fragment shape.

[0177] The smaller the particle size of the carbon for filtering, the larger the surface area. As a result, the probability of contact with the additive under physical and chemical action and the adsorption efficiency may be excessively increased. In the case where the particle size of the carbon for filtering is too small, there is a problem of adsorbing effective organic additives in addition to organic impurities. Therefore, the carbon for filtering needs to have an appropriate particle size. Granular carbon and fragment carbon are suitable for carbon filtration because they can only filter impurities of organic additives.

[0178] Specifically, carbon filtration can be performed by adding granular carbon and / or fragmentary carbon to an organic additive and stirring. The organic additive is added to the filtration carbon filtration. At this time, the added water-soluble organic additive is made into a solution with a concentration of 5000 to 50000 ppm with distilled water, and granular carbon or fragmentary carbon is added at a concentration of 2 to 10 g / L.

[0179] When the concentration of the organic additive is less than 5000 ppm, carbon filtration takes a long time, and when it exceeds 50000 ppm, the effect of carbon filtration is weak, and impurities cannot be sufficiently removed.

[0180] When the concentration of granular carbon and / or fragmented carbon is less than 2 g / L, the carbon filtration effect is weak, so the required time increases and impurities cannot be fully removed. On the other hand, when it exceeds 10 g / L, since effective organic additives are also adsorbed, not only the desired physical properties of the copper foil cannot be obtained, but also the deviation of the physical properties increases.

[0181] By circulating the organic additive solution to which the granular carbon or the flake carbon is added for 30 to 90 minutes, the organic impurities present in the organic additive can be removed, thereby reducing the total organic carbon (TOC) of the electrolyte.

[0182] When using an organic additive that has been carbon filtered, an electrolytic copper foil having a ratio of tensile strength after heat treatment at 190°C for 60 minutes to tensile strength at room temperature of 0.950 or more can be produced. In addition, by carbon filtering of the organic additive, the tensile strength of the electrolytic copper foil after heat treatment at 190°C for 60 minutes can be made to be 40.0 kgf / mm 2 above.

[0183] Diatomaceous earth filtration is to use diatomaceous earth to remove organic impurities and inorganic impurities of organic additives. Specifically, diatomaceous earth can be added to a filter tank to form a diatomaceous earth filter bag, and organic additives can be added to perform filtration.

[0184] Ozone treatment is to treat the electrolyte with ozone (O3) to maintain the purity of the organic additive. Specifically, for example, in a filter tank equipped with an ozone generator, organic and inorganic impurities can be decomposed and removed by ozone. The ozone-treated solution is preferably filtered again with diatomaceous earth.

[0185] For the purity of the electrolyte, the copper wire (Cu wire) used as a raw material of the electrolyte may be cleaned.

[0186] According to one embodiment of the present invention, the step of preparing the electrolyte may include: a step of heat treating the copper wire; a step of pickling the heat treated copper wire; a step of water washing the pickled copper wire; and a step of putting the water washed copper wire into sulfuric acid for the electrolyte.

[0187] More specifically, in order to maintain the purity of the electrolyte, a high-purity (99.9% or more) copper wire is heat-treated in an electric furnace at 750°C to 850°C to burn off various organic impurities attached to the copper wire, and then the copper wire heat-treated for 10 to 20 minutes is pickled using a 10% sulfuric acid solution, and the pickled copper wire is washed with distilled water, thereby manufacturing copper for the electrolyte. The electrolyte can be prepared by putting the washed copper wire into sulfuric acid for the electrolyte.

[0188] According to an embodiment of the present invention, in order to meet the characteristics of the electrolytic copper foil, the concentration of total organic carbon (TOC) in the electrolyte is controlled to be less than 50 ppm. That is, the electrolyte may have a total organic carbon (TOC) concentration of less than 50 ppm.

[0189] As the TOC concentration in the electrolyte increases, the amount of carbon (C) elements flowing into the copper layer increases, and accordingly, the amount of all elements desorbed from the copper layer during heat treatment increases, resulting in a decrease in the strength of the electrolytic copper foil after heat treatment.

[0190] According to one embodiment of the present invention, a certain amount of carbon (C), hydrogen (H), nitrogen (N) or sulfur (S) can be co-precipitated in the copper layer by adjusting the concentration of organic additives added to the electrolyte, especially organic additives containing nitrogen (N) or sulfur (S), or removing organic impurities. The orientation index of the copper layer can be controlled by this co-precipitation.

[0191] The copper layer produced in the manner described above may be cleaned in a cleaning tank.

[0192] For example, acid cleaning for removing impurities on the surface of the copper layer, such as resin components or natural oxide, and water cleaning for removing the acid solution used in the acid cleaning may be performed in sequence. The cleaning step may also be omitted.

[0193] Through these steps, electrolytic copper foil can be produced.

[0194] According to an embodiment of the present invention, the method for manufacturing the electrolytic copper foil may further include a step of forming a protective layer on the copper layer using an anti-rust liquid.

[0195] Through the step of forming the protective layer, at least one protective layer is formed on the copper layer.

[0196] The copper layer is immersed in the anti-rust liquid contained in the anti-rust tank to form a protective layer on the copper layer. The anti-rust liquid may contain at least one of chromium (Cr), a silane compound and a nitrogen compound, and chromium may exist in an ionic state in the anti-rust liquid.

[0197] The concentration of at least one of chromium (Cr), silane compounds and nitrogen compounds contained in the rust-proof liquid may be 1 to 10 g / L. In order to form the protective layer, the temperature of the rust-proof liquid may be maintained at 20 to 40° C. The copper layer may be immersed in the rust-proof liquid for about 1 to 30 seconds.

[0198] When the concentration of at least one of chromium (Cr), silane compounds and nitrogen compounds in the rust-proof liquid is less than 1 g / L, the protective layer will not be able to play a role in protecting the copper layer, and the corrosion of the copper layer will be accelerated, resulting in the breakage of the electrolytic copper foil. On the contrary, when the concentration exceeds 10 g / L, it exceeds the necessary amount for obtaining the electrolytic copper foil having the rust-proof performance of the present invention, and thus the economy and efficiency will be reduced.

[0199] By forming such a rust-proof film, an electrolytic copper foil including a protective layer is manufactured.

[0200] Then, the electrolytic copper foil is cleaned in a cleaning tank. This cleaning step can be omitted.

[0201] Then, after a drying process is performed, the electrolytic copper foil is wound up on a winder (WR).

[0202] The electrode for a secondary battery of the present invention (ie, negative electrode) can be produced by coating a negative electrode active material on the electrolytic copper foil of the present invention produced in the above-described manner.

[0203] The negative electrode active material may be selected from the group consisting of carbon; Si, Ge, Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe metal; an alloy containing the metal; an oxide of the metal; and a composite of the metal and carbon.

[0204] For example, 1 to 3 parts by weight of styrene-butadiene rubber (SBR) and 1 to 3 parts by weight of carboxymethyl cellulose (CMC) are mixed with 100 parts by weight of carbon for negative electrode active material, and then distilled water is used as a solvent to prepare a slurry. Next, the slurry is applied to the electrolytic copper foil 110 with a thickness of 20 to 100 μm using a scraper, and the slurry is heated at 110 to 130° C. at a temperature of 0.5 to 1.5 ton / cm 2 pressure.

[0205] A lithium secondary battery can be manufactured using a conventional positive electrode, electrolyte, and separator together with the secondary battery electrode (negative electrode) of the present invention manufactured by the above method.

[0206] Hereinafter, the present invention will be specifically described by way of examples and comparative examples. However, the following examples and comparative examples are only used to help understanding of the present invention, and the scope of rights of the present invention is not limited to the examples or comparative examples.

[0207] Examples 1 to 4 and Comparative Examples 1 to 5

[0208] Electrolytic copper foil is manufactured using a foil making machine including an electrolytic cell, a rotating cathode roller arranged in the electrolytic cell, and an anode plate arranged separately from the rotating cathode roller. The electrolyte is a copper sulfate solution. The copper ion concentration in the electrolyte is set to 85 g / L, the concentration of sulfuric acid is set to 105 g / L, the average temperature of the electrolyte is set to 55°C, and the current density is set to 60 ASD.

[0209] In addition, the presence or absence of carbon filtration, the type and concentration of organic additives contained in the electrolyte, and the chloride ion (Cl - ) concentrations are shown in Table 1 below.

[0210] In Examples 1 to 4 and Comparative Examples 1, 3, and 4, the organic additives were pretreated by carbon filtration before being added to the electrolyte. Granular carbon was used in the carbon filtration. The added water-soluble organic additive was made into a solution with a concentration of 50,000 ppm in distilled water, and granular carbon was added at a concentration of 10 g / L. Carbon filtration was performed by circulating the organic additive solution for 60 minutes.

[0211] In the following Table 1, the case where carbon filtration was performed is indicated by "Y", and the case where carbon filtration was not performed is indicated by "N".

[0212] As the collagen in the organic additive, collagen having a molecular weight of 2000 to 7000 and a cysteine ​​structure is used. In addition, as the gelatin, gelatin having a molecular weight of 4000 to 15000 and a cysteine ​​structure is used.

[0213] A current is applied between the rotating cathode drum and the anode plate at a current density of 60 ASD to produce a copper layer. Then, the copper layer is immersed in a rust-proof liquid for about 2 seconds to perform a chromate treatment on the surface of the copper layer to form a first protective layer and a second protective layer, thereby producing an electrolytic copper foil. As the rust-proof liquid, a rust-proof liquid with chromic acid as the main component is used, and the concentration of chromic acid is 5 g / L.

[0214] As a result, electrolytic copper foils of Examples 1 to 4 and Comparative Examples 1 to 5 were produced. The thickness of the electrolytic copper foils was the same 8 μm.

[0215] [Table 1]

[0216]

[0217] Gelatin

[0218] ColA: collagen

[0219] The electrolytic copper foils of Examples 1 to 4 and Comparative Examples 1 to 5 manufactured as described above were measured for (i) the orientation index [M(220)] of the (220) plane, (ii) the elongation (normal temperature), (iii) the tensile strength at normal temperature and the tensile strength after heat treatment, and (iv) the ratio of the tensile strength after heat treatment at 190°C for 60 minutes to the tensile strength at normal temperature. In addition, (v) the cross section of the electrolytic copper foil was photographed and analyzed by EBSD.

[0220] In addition, after a secondary battery was manufactured using the electrolytic copper foil and the secondary battery was charged and discharged, (vi) the secondary battery was disassembled to observe whether wrinkles were present.

[0221] (i) Determination of the orientation index of the (220) plane [M(220)]

[0222] The orientation index [M(220)] of the (220) plane of the electrolytic copper foils produced in Examples 1-4 and Comparative Examples 1-5 was determined by the following formula 1.

[0223] [Formula 1]

[0224] M(220)=IR(220) / IFR(220)

[0225] In the above formula 1, IR(220) and IFR(220) are obtained by the following formula 2 and the following formula 3, respectively.

[0226] [Formula 2]

[0227]

[0228] [Formula 3]

[0229]

[0230] In Formula 2, I(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of the electrolytic copper foil 101, and I(220) is the XRD diffraction intensity of the (220) plane of the electrolytic copper foil 101. In Formula 3, IF(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of a standard sample with no orientation relative to all crystal planes as specified by JCPDS (Joint Committee on Powder Diffraction Standards), and IF(220) is the XRD diffraction intensity of the (220) plane of the standard sample.

[0231] In order to measure the relative diffraction intensity [IR(hkl)] with respect to a specific crystal plane (hkl) of the copper layer, first, an XRD spectrum having peaks corresponding to each crystal plane was obtained by X-ray diffraction (XRD) in the diffraction angle range (2θ) of 30° to 95° [target: copper Kα1, 2θ spacing: 0.01°, 2θ scanning speed: 1° / min].

[0232] An XRD spectrum including four peaks corresponding to the (111) plane, the (200) plane, the (220) plane, and the (311) plane is obtained from the copper layer 110. Then, the XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) is obtained from the spectrum. The XRD diffraction intensity [I(hkl)] of each crystal plane (hkl) obtained by the above method is substituted into the formula 2 to calculate the relative diffraction intensity [IR(220)] relative to the specific crystal plane (220) of the copper layer 110.

[0233] In addition, the relative diffraction intensity [IFR(220)] of a specific crystal plane (220) obtained from a standard sample that is not oriented relative to all crystal planes can be calculated by substituting the XRD diffraction intensity [IF(hkl)] of each crystal plane (hkl) of the standard sample that is not oriented relative to all crystal planes specified by JCPDS into the above formula 3.

[0234] (ii) Determination of elongation at room temperature

[0235] The elongation at room temperature (25±15° C.) of the electrolytic copper foils produced in Example 1-4 and Comparative Example 1-5 was measured.

[0236] The elongation was measured using a universal testing machine (UTM) according to the IPC-TM-650 Test Method Manual. Specifically, the elongation was measured using a universal testing machine from Instron. The width of the sample for elongation measurement was 12.7 mm, the distance between the grips was 50 mm, and the measurement speed was 50 mm / min.

[0237] (iii) Determination of tensile strength at room temperature and after heat treatment

[0238] The tensile strength of the electrolytic copper foils produced in Examples 1-4 and Comparative Examples 1-5 was measured at room temperature (25±15° C.), and the tensile strength of the electrolytic copper foils after heat treatment at 190° C. for 60 minutes was measured.

[0239] According to the provisions of the IPC-TM-650 Test Method Manual, the tensile strength at room temperature and after heat treatment was measured using a universal testing machine (UTM). Specifically, the tensile strength at room temperature and the tensile strength after heat treatment were measured using a universal testing machine from Instron. The width of the sample for elongation measurement was 12.7 mm, the distance between the grips was 50 mm, and the measurement speed was 50 mm / min.

[0240] (iv) Ratio of the tensile strength after heat treatment at 190°C for 60 minutes to the tensile strength at room temperature

[0241] The ratio of the tensile strength after heat treatment at 190° C. for 60 minutes to the tensile strength at room temperature was calculated using the tensile strength at room temperature and the tensile strength after heat treatment of the electrolytic copper foils produced in Examples 1-4 and Comparative Examples 1-5 measured above.

[0242] (v) EBSD cross section of electrolytic copper foil

[0243] An electron backscatter diffraction (EBSD) imaging device was used to photograph the cross sections of the electrolytic copper foils produced in Example 1 and Example 2. Each electrolytic copper foil was photographed twice after heat treatment at room temperature and 190° C. for 1 hour.

[0244] Specifically, the shooting conditions and shooting steps are as follows:

[0245] 1. Fix the sample and perform cross-section hot mounting

[0246] 2. Mechanical grinding

[0247] 3. Mount the sample on the SEM equipment and measure the cross section at an inclination of 70 degrees

[0248] 4. Determine each orientation

[0249] EBSD imaging equipment: Hitachi S-4300SE

[0250] Analysis program: OIM analysis 7.0

[0251] In the photographs of Example 1 taken by the method described above, the photographs at room temperature are as follows: Fig.10 , the photos after heat treatment are as follows Fig.11 In addition, in the photos taken in Example 2, the photos taken at room temperature are as follows: Fig.12 , the photos after heat treatment are as follows Fig.13 .

[0252] (vi) Is there any wrinkle on the electrolytic copper foil?

[0253] 1) Anode manufacturing

[0254] 2 parts by weight of styrene-butadiene rubber (SBR) and 2 parts by weight of carboxymethyl cellulose (CMC) were mixed with 100 parts by weight of commercially available silicon / carbon composite negative electrode material for negative electrode active material, and distilled water was used as a solvent to prepare a slurry for negative electrode active material. The slurry for negative electrode active material was applied to the electrolytic copper foil of Examples 1-4 and Comparative Examples 1-5 with a width of 10 cm using a scraper at a thickness of 40 μm, dried at 120°C, and applied with 1 ton / cm 2 of pressure, thereby manufacturing a negative electrode for a secondary battery.

[0255] 2) Preparation of electrolyte

[0256] The base electrolyte was prepared by dissolving LiPF6 as a solute at a concentration of 1 M in a non-aqueous organic solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a ratio of 1:2. The non-aqueous electrolyte was prepared by mixing 99.5 wt % of the base electrolyte and 0.5 wt % of succinic anhydride.

[0257] 3) Cathode manufacturing

[0258] Lithium manganese oxide Li 1.1 Mn 1.85 Al 0.05 O4 and lithium manganese oxide o-LiMnO2 having an orthorhombic crystal structure are mixed in a ratio of 90:10 (weight ratio) to produce a positive electrode active material. The positive electrode active material, carbon black, and poly (vinylidene fluoride) [PVDF: Poly (vinylidene fluoride)] as a binder are mixed in a ratio of 85:10:5 (weight ratio), and mixed with NMP as an organic solvent to prepare a slurry. The slurry prepared as described above is applied to both sides of an Al foil having a thickness of 20 μm, and then dried to produce a positive electrode.

[0259] 4) Manufacturing of lithium secondary batteries for testing

[0260] The positive electrode and the negative electrode are arranged in an insulated manner inside the aluminum can, and a non-aqueous electrolyte and a separator are arranged between them, thereby manufacturing a coin-shaped lithium secondary battery. The separator used is polypropylene (Celgard 2325; thickness: 25 μm, average pore size: Porosity: 40%).

[0261] 5) Charging and discharging of secondary batteries

[0262] The lithium secondary battery manufactured as described above was used to drive the battery at a charge voltage of 4.3 V and a discharge voltage of 3.4 V, and was charged / discharged 100 times at a high temperature of 50° C. and a current rate (C-rate) of 0.2.

[0263] 6) Whether wrinkles or tears occur

[0264] After 100 cycles of charge and discharge, the secondary battery was disassembled to observe whether wrinkles or tears occurred in the copper foil. The case where wrinkles or tears occurred in the copper foil was marked as "occurred", and the case where wrinkles or tears did not occur was marked as "none".

[0265] The above test results are shown in Table 2.

[0266] [Table 2]

[0267]

[0268] With reference to Table 2, the following results can be confirmed.

[0269] Comparative Example 1 is an example in which gelatin is added in a small amount of 0.3 ppm to the grain regulator. The tensile strength after heat treatment is 30.4 kgf / mm 2 The ratio of the tensile strength after heat treatment to the tensile strength at room temperature is 0.738, and wrinkles occur.

[0270] Comparative Examples 2 and 5 are examples without carbon filtration. The orientation index [M(220)] of the (220) surface of Comparative Example 2 is 0.8, the elongation is 1.7%, and wrinkles occur. The orientation index [M(220)] of the (220) surface of Comparative Example 5 is 0.9, the elongation is 1.9%, and the tensile strength at room temperature is 40.7 kgf / mm 2 , the tensile strength after heat treatment is 38.8kgf / mm 2 , wrinkles occur.

[0271] Comparative Example 3 is to add excessive chloride ions (Cl - ) concentration is 1.6ppm, the orientation index [M(220)] of the (220) plane is 0.8, and the tensile strength at room temperature is 40.0kgf / mm 2 , the tensile strength after heat treatment is 34.9kgf / mm 2 The ratio of the tensile strength after heat treatment to the tensile strength at room temperature is 0.873, and wrinkles occur.

[0272] Comparative Example 4 is an example in which an excess amount of collagen is added to the grain regulator at 25 ppm. The tensile strength after heat treatment is 67.8 kgf / mm 2, wrinkles occur.

[0273] On the other hand, in the electrolytic copper foils of Examples 1 to 4 of the present invention, all numerical values ​​were within the range of the reference value, and wrinkles were not generated in any of them.

[0274] The present invention described above is not limited to the aforementioned embodiments and drawings. It is obvious to those skilled in the art that various substitutions, deformations or changes can be made within the scope of the technical content of the present invention. Therefore, the scope of the present invention is expressed by the claims, and it should be interpreted that all changes or deformations derived from the meaning, scope and equivalent concepts of the claims are included in the scope of the present invention.

Claims

1. An electrolytic copper foil, wherein: Including copper layer, The copper layer has a (220) plane in a cross section of the electrolytic copper foil along a thickness direction, and an orientation index [M(220)] of the (220) plane is 2.8 to 3.

4. The orientation index [M(220)] is obtained by the following formula 1: Formula 1 M(220)=IR(220) / IFR(220) In the formula 1, the IR (220) and the IFR (220) are obtained by the following formula 2 and the following formula 3, respectively. Formula 2 Formula 3 In Formula 2, I(hkl) is the XRD diffraction intensity of each crystal plane (hkl) of the electrolytic copper foil, In Formula 3, IF(hkl) is the XRD diffraction intensity of each crystal plane (hkl) in the JCPDS card.

2. The electrolytic copper foil according to claim 1, wherein It has an elongation of 2 to 15% at room temperature.

3. The electrolytic copper foil according to claim 1, wherein At room temperature, it has a range of 41.0 to 75.0 kgf / mm 2 tensile strength.

4. The electrolytic copper foil according to claim 1, wherein 40.0 to 65.0 kgf / mm after heat treatment at 190°C for 60 minutes 2 tensile strength.

5. The electrolytic copper foil according to claim 1, wherein The ratio of the tensile strength after heat treatment at 190°C for 60 minutes to the tensile strength at room temperature is 0.950 or more.

6. The electrolytic copper foil according to claim 1, wherein The thickness is 2.0 to 18.0 μm.

7. The electrolytic copper foil according to claim 1, wherein Also includes a protective layer configured on the copper layer, The protective layer includes at least one of chromium, a silane compound, and a nitrogen compound.

8. An electrode for a secondary battery, wherein: include: Electrolytic copper foil; as well as The active material layer is disposed on at least one side of the electrolytic copper foil. The electrolytic copper foil is the electrolytic copper foil according to any one of claims 1 to 7.

9. A secondary battery, wherein: include: positive electrode; negative electrode; An electrolyte, disposed between the positive electrode and the negative electrode, providing an environment enabling lithium ions to move; as well as A separator to electrically insulate the positive electrode from the negative electrode, The negative electrode is composed of the electrode for a secondary battery according to claim 8.

10. A method for producing an electrolytic copper foil, wherein: include: a step of preparing an electrolyte solution comprising copper ions and an organic additive; as well as The step of forming a copper layer by electrifying the anode plate and the rotating cathode drum which are arranged in a spaced-apart manner in the electrolyte at a current density, The method further comprises the step of purifying the organic additive by at least one of carbon filtration, diatomaceous earth filtration and ozone treatment. The step of preparing the electrolyte comprises: The step of heat treating the copper wire; A step of pickling the heat-treated copper wire; The step of washing the pickled copper wire with water; and The step of placing the washed copper wire into sulfuric acid as an electrolyte, The electrolyte comprises: 80 to 120 g / L of copper ions; 80 to 150 g / L sulfuric acid; and 0.3 to 0.5 ppm of chloride ion (Cl - ), The organic additives include a grain regulator, The grain regulator includes an organic compound having an amino group, a carboxyl group (—COOH), and a mercapto group (—SH).

11. The method for producing an electrolytic copper foil according to claim 10, wherein: The carbon filtration uses at least one of granular carbon and flake carbon.

12. The method for producing an electrolytic copper foil according to claim 10, wherein: The concentration of the grain regulator is 0.5 to 15.0 ppm.

13. The method for producing an electrolytic copper foil according to claim 10, wherein: The electrolyte has a total organic carbon concentration of 50 ppm or less.

14. The method for producing an electrolytic copper foil according to claim 10, wherein: The step further includes: forming a protective layer on the copper layer using an anti-rust liquid, The rust-proof liquid contains at least one of chromium, a silane compound and a nitrogen compound.

Citation Information

Patent Citations

  • Electrolytic foil and producing method thereof

    CN102168289A

  • Anti-creasing copper foil, electrode comprising same, secondary battery comprising same, and manufacturing method therefor

    CN110997983A

  • High-tensile electrolytic copper foil and process for producing the same

    CN1193360A